Molecular Targets for the Treatment of Juvenile Myelomonocytic Leukemia - Xiaoling Liu; Himalee Sabnis; Kevin D. Bunting; Cheng-Kui Qu (Advances in Hematology)
Significant advances in our understanding of the genetic defects and the pathogenesis of juvenile myelomonocytic leukemia (JMML) have been achieved in the last several years. The information gathered tremendously helps us in designing molecular targeted therapies for this otherwise fatal disease. Various approaches are being investigated to target defective pathways/molecules in this disease. However, effective therapy is still lacking. Development of specific target-based drugs for JMML remains a big challenge and represents a promising direction in this field.